Gut microbiota in patients with COVID-19 and type 2 diabetes: A culture-based method - Petakh, Pavlo; Kobyliak, Nazarii; Kamyshnyi, Aleksandr (Frontiers in Cellular and Infection Microbiology, 2023)
Background The global pandemic of coronavirus disease 2019 (COVID-19) continues to affect people around the world, with one of the most frequent comorbidities being Type 2 Diabetes (T2D). Studies have suggested a link between disbalances in gut microbiota and these diseases, as well as with COVID-19, potentially due to inflammatory dysfunction. This study aims to analyze the changes in gut microbiota in COVID-19 patients with T2D using a culture-based method. Methods The stool samples were taken from 128 patients with confirmed COVID-19. Changes in the composition of gut microbiota were analyzed by culture-based method. The study used chi-squared and t-test to find significant differences in gut bacteria between samples and non-parametric correlation analysis to examine relationship between gut bacteria abundance, C‐reactive protein (CRP) levels and length of stay (LoS) in COVID-19 patients without T2D. Results The gut microbiota of T2D patients with COVID-19 showed increased Clostridium spp., Candida spp., and decreased Bifidobacterium spp., Lactobacillus spp. Metformin-treated patients with T2D and COVID-19 without antibiotic treatment showed increased Bacteroides spp., Lactobacillus spp., and decreased Enterococcus, Clostridium compared to the same group with antibiotic treatment. The study also found a positive correlation between the abundance of certain gut microbiota genera, such as Klebsiella spp. and Enterococcus spp., and CRP levels and LoS in COVID-19 patients without and with T2D, while the abundance of other genera, such as Bifidobacterium spp. and Lactobacillus spp., was found to have a negative correlation. Conclusion In conclusion, this study provides important insights into the gut microbiota composition of SARS-CoV-2-infected individuals with T2D and its potential impact on the course of the disease. The findings suggest that certain gut microbiota genera may be associated with increased CRP levels and longer hospital stays. The significance of this study lies in the fact that it highlights the potential role of gut microbiota in the progression of COVID-19 in patients with T2D, and may inform future research and treatment strategies for this patient population. The future impact of this study could include the development of targeted interventions to modulate gut microbiota in order to improve outcomes for COVID-19 patients with T2D.